Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/23311932.2016.1183457
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of bio-inoculants and organic matter for the management of root-knot nematode infesting chickpea

Abstract: A pot experiment was conducted during 2013-14 to observe the potential role of some organics and bio-organics such as Calotropis procera, Glomus fasciculatum, and Azotobacter chroococcum on some growth attributes of chickpea and subsequently on the root-knot development caused by Meloidogyne incognita. Individual and conjoint treatments significantly enhanced the plant growth parameters as compared to unamended control. Physiological parameter such as chlorophyll content also exhibited significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Moreover, A. chroococcum either single or combined with NPK treatments showed the greatest increase in number of pods, in addition NPK + Az combined treatment exhibited significant increase in pods weight, weight of 200 seeds, peanut crop production and oil content. This result is in harmony with the finding of Akram et al (2016) who indicated that the application of A. chroococcum singly or combined with Glomus fasciculatum significantly increased growth parameters of chickpea plant infected with M. incognita than the control. These results could be discussed on the basis that soil bacteria Azotobacter, has been reported to produce growth promoting substances as auxins, cytokine, gibberellins and these bioactive compounds stimulate plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, A. chroococcum either single or combined with NPK treatments showed the greatest increase in number of pods, in addition NPK + Az combined treatment exhibited significant increase in pods weight, weight of 200 seeds, peanut crop production and oil content. This result is in harmony with the finding of Akram et al (2016) who indicated that the application of A. chroococcum singly or combined with Glomus fasciculatum significantly increased growth parameters of chickpea plant infected with M. incognita than the control. These results could be discussed on the basis that soil bacteria Azotobacter, has been reported to produce growth promoting substances as auxins, cytokine, gibberellins and these bioactive compounds stimulate plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Among the fungal biofertilizers, phosphate solubilizing mycorrhizal fungi has reported to make best consortium with Azotobacter in enhancing plant growth attributes ( Behl et al, 2003 ). Synergistic interaction between the free-living nitrogen fixing bacteria, Azotobacter and AM fungus, Glomus are reported by several workers ( Ishac et al, 1986 , Akram et al, 2016 ). Bagyaraj and Menge (1978) studied the impact of inoculating tomato plants with Glomus fasciculatum and Azotobacter chroococcum either individually or concomitantly on the population of rhizospheric bacteria.…”
Section: Current Trend In Utilization Of Azotobacter mentioning
confidence: 82%
“…Such hormones stem from the rhizosphere or root surface and impose positive effects on the growth of the higher plants growing in the nearby areas. Barakat and Gabr, 1998 , Puertas and Gonzales, 1999 , Baral and Adhikari, 2013 , Akram et al, 2016 observed that plant dry weight of different crops like tomato, maize and chickpea was considerably greater on the application of Azotobacter chroococcum as compared to un-inoculated plants.…”
Section: Plant Growth Promotion Activities Of Azotobacter mentioning
confidence: 99%
See 1 more Smart Citation
“…Dual inoculation of biofertilizers and neem cake along with a 100% recommended dose of nitrogenous fertilizer brought about a greater reduction in root-knot development as well as the multiplication of plant-parasitic nematodes. Akram et al (2016) found that disease incidence by the root-knot nematode Meloidogyne incognita was significantly reduced when A. chroococcum was applied to chickpea plants. Several mechanisms can be implicated in the management strategies used by bacteria for the control of plant diseases.…”
Section: Discussionmentioning
confidence: 99%